2022
DOI: 10.1002/bse.3275
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of firms' greenness towards sustainable development: A multi‐country analysis

Abstract: A higher greenness of firms is crucial for the mitigation of climate change and other environmental pollution problems. This paper analyses the drivers of a greening of firms from a theoretical and empirical perspective. Three theoretical concepts—the stakeholder theory, the institutional theory and the resource‐based view—contribute to identifying the determinants of firms' greenness. In our empirical analysis based on recent World Bank data, greenness is measured by different environmentally related measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 72 publications
3
23
1
Order By: Relevance
“…Not only the development of the world's population but also constant changes in the climate, ecosystems and the business environment, as well as their harmful effects on society (Chalupa et al 2021;Lee and Trimi 2021) emphasise the need to address responsible and sustainable innovation across a broad context (Saha et al 2017;Cillo et al 2019;Horbach et al 2022), using a knowledge approach (Hadj 2020). This applies to all sectors, including agriculture, forestry and food.…”
mentioning
confidence: 99%
“…Not only the development of the world's population but also constant changes in the climate, ecosystems and the business environment, as well as their harmful effects on society (Chalupa et al 2021;Lee and Trimi 2021) emphasise the need to address responsible and sustainable innovation across a broad context (Saha et al 2017;Cillo et al 2019;Horbach et al 2022), using a knowledge approach (Hadj 2020). This applies to all sectors, including agriculture, forestry and food.…”
mentioning
confidence: 99%
“…This is in addition to their focus on building long-term relationships and maintaining guest loyalty (Assaker 2020). Sustainable development is based on three pillars (Klarin 2018;Horbach et al 2022): the concept of development (socio-economic development following environmental constraints), the concept of needs (allocation of resources to increase the quality of life), and the concept of future generations (sustainable use of resources in line with the needs of future generations). add that it is about managing the triple profit, which Belz and Binder (2017) define in the definition of sustainable business as economic, social, and ecological.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar to stakeholder theory, institutional theory suggests that firms must conform to different institutional forces in their decision‐making related to ecological development (Horbach et al, 2022; Zhang, Tay, et al, 2022). These pressures from different stakeholders can be understood as coercive, normative, and mimetic pressures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Passaro et al (2022), meanwhile, suggested that the size of enterprises will cause the driving effects of stakeholders on ecological development to be different. Similar to stakeholder theory, institutional theory suggests that firms must conform to different institutional forces in their decisionmaking related to ecological development (Horbach et al, 2022;Zhang, Tay, et al, 2022). These pressures from different stakeholders can be understood as coercive, normative, and mimetic pressures.…”
Section: Drivers Of Enterprises' Ecological Development Practicesmentioning
confidence: 99%
See 1 more Smart Citation